A Seed-Endophytic Bacillus safensis Strain With Antimicrobial Activity Has Genes for Novel Bacteriocin-Like Antimicrobial Peptides - Romero-Severson, Jeanne; Moran, Thomas E.; Shrader, Donna G.; Fields, Francisco R.; Pandey-Joshi, Susan; Thomas, Clayton L.; Palmer, Emily C.; Shrout, Joshua D.; Pfrender, Michael E.; Lee, Shaun W. (Frontiers in Microbiology, 2021)
Bacteriocins are a highly diverse group of antimicrobial peptides that have been identified in a wide range of commensal and probiotic organisms, especially those resident in host microbiomes. Rising antibiotic resistance have fueled renewed research into new drug scaffolds such as antimicrobial peptides for use in therapeutics. In this investigation, we examined mung bean seeds for endophytes possessing activity against human and plant pathogens. We isolated a novel strain of Bacillus safensis, from the contents of surface-sterilized mung bean seed, which we termed Bacillus safensis C3. Genome sequencing of C3 identified three distinct biosynthetic systems that produce bacteriocin-based peptides. C3 exhibited antibacterial activity against E. coli, Xanthomonas axonopodis and Pseudomonas syringae. Robust antimicrobial activity of B. safensis C3 was observed when C3 was co-cultured with Bacillus subtilis. Using the cell-free supernatant of C3 and cation exchange chromatography, we enriched a product that retained antimicrobial activity against B. subtilis. The peptide was found to be approximately 3.3 kDa in size by mass spectrometry, and resistant to proteolysis by Carboxypeptidase Y and Endoproteinase GluC, suggesting that it is a modified variant of an AS-48 like bacteriocin. Our findings open new avenues into further development of novel bacteriocin-based scaffolds for therapeutic development, as well as further investigations into how our discoveries of bacteriocin-producing plant commensal microorganisms may have the potential for an immediate impact on the safety of food supplies.